Acinar cystic transformation of the pancreatic body and tail in an elderly male patient: A case report - Anubhav Narwal; Rajesh Panwar; Kumble S. Madhusudhan; Sujoy Pal; Prasenjit Das (Indian Journal of Pathology and Microbiology, 2023)
Acinar cystic transformation (ACT) is a rare benign cystic lesion of the pancreas reported in elderly women. ACT can be easily confused with other cystic lesions of the pancreas, such as intraductal papillary neoplasm and serous and mucinous neoplasms, on imaging, especially when detected radiologically in a male patient as the index case. A preoperative histological examination can establish a diagnosis and avoid extensive surgical resection. We hereby report a case of ACT in a 69-year-old male patient that affected the body and tail region of the pancreas.